Safety and hygiene practices in handling and provision of food among catering students, FPTV - Ahmad, Nor Aziah; Zainuddin, Nazatul Syuhada (Penerbit UTHM, 2021)
This safety practice is also practiced by food operators in food preparation. Food operators are individuals involved in the preparation of food starting from preparing food until the food is served to customers. Food operators also cover the preparation, presentation and sale of food (Bhat & Gomez-Lopez, 2014). As a good operator, safety and hygiene practices should be applied when preparing the food. Additionally, every food handler also needs to keep themselves clean and tidy. According to the National Food Act 1983, each food operator should be present in the Food Controller Training to make sure they are vulnerable to these safety and hygiene practices. With these exercises, indirect food operators are knowledgeable and can also be used by them to ensure that the food produced is clean and free of any harm (Kamal, Hashim, & Adnan, 2015). This is because, with these safety and hygiene practices can prevent food from being tainted. In addition to preventing food from being exposed to hazards. When the food is contaminated, it will result in the customer taking the food exposed to the risk of suffering from ailments. Therefore, this safety can be used as a guide to food operators. Based on these safety and hygiene practices, the operator can make sure that the food is safe and free of any pollution and damage. Safe food can guarantee the health of the person who takes the food.